2021
DOI: 10.1002/ece3.8150
|View full text |Cite
|
Sign up to set email alerts
|

How many replicates to accurately estimate fish biodiversity using environmental DNA on coral reefs?

Abstract: Quantifying fish species diversity in rich tropical marine environments remains challenging. Environmental DNA (eDNA) metabarcoding is a promising tool to face this challenge through the filtering, amplification, and sequencing of DNA traces from water samples. However, because eDNA concentration is low in marine environments, the reliability of eDNA to detect species diversity can be limited. Using an eDNA metabarcoding approach to identify fish Molecular Taxonomic Units (MOTUs) with a single 12S marker, we a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 89 publications
3
42
0
Order By: Relevance
“…However, our site-based and station-based accumulation curves do not reach plateaus suggesting that our sampling effort was not sufficient to exhaustively estimate fish biodiversity for each site (electronic supplementary material, analyses, figure S5) and station (electronic supplementary material, analyses, figure S6). Twentyfive replicates (so, 12 stations in case of field duplicates) could accurately estimate biodiversity regionally due to high local turnover [53]. A higher number of eDNA samples would be necessary here to reach MOTU accumulation per site and station.…”
Section: Discussionmentioning
confidence: 99%
“…However, our site-based and station-based accumulation curves do not reach plateaus suggesting that our sampling effort was not sufficient to exhaustively estimate fish biodiversity for each site (electronic supplementary material, analyses, figure S5) and station (electronic supplementary material, analyses, figure S6). Twentyfive replicates (so, 12 stations in case of field duplicates) could accurately estimate biodiversity regionally due to high local turnover [53]. A higher number of eDNA samples would be necessary here to reach MOTU accumulation per site and station.…”
Section: Discussionmentioning
confidence: 99%
“…However, replication quality and sampling effort may vary according to the studied environment because biotic and abiotic conditions can influence degradation, deposition and detection of eDNA (Stewart, 2019). For example in highly diverse tropical marine ecosystems where eDNA shedding and decay rates tend to be higher, partially due to higher water temperature (Jo et al, 2019), a study by Stauffer et al (2021) highlighted strong dissimilarity in species composition between filtration replicates (e.g., dissimilarity β jac mean = 0.729 ± 0.102 in the West Indian Ocean; β jac mean = 0.528 ± 0.146 in the Caribbean Sea, with a major contribution of the turnover component for both sampling areas) and required additional sampling efforts to ensure robust biodiversity estimates.…”
Section: Fine-scale Diversity Patternsmentioning
confidence: 99%
“…Adequate water-sampling procedures for aquatic ecosystems are important for eDNA studies. Previous research has demonstrated that a large volume of filtration water is needed to represent real fauna in habitats ( Cantera et al, 2019 ; Polanco et al, 2021 ; Pont et al, 2018 ; Stauffer et al, 2021 ; Valentini et al, 2016 ). The three filtration water volumes tested in this study are commonly used in eDNA metabarcoding studies, with high success rates for species detection ( Sales et al, 2021 ; Valdivia-Carrillo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, different extraction techniques can result in differences in DNA quantity and quality, which can subsequently impact biodiversity assessment ( Coutant et al, 2021 ; Deiner et al, 2015 ; Jeunen et al, 2019 ; Piggott, 2016 ; Wittwer et al, 2018 ). At present, studies show considerable variation in the protocols and steps involved in aquatic eDNA metabarcoding, which can impact the probability of detecting species as the protocols are not specific for fish and quantitative standards for estuarine ecosystems are lacking ( Kumar et al, 2020 ; Lear et al, 2018 ; Stauffer et al, 2021 ). Thus, understanding the differences in DNA yields generated by different protocol combinations is essential for the successful application of eDNA metabarcoding in estuarine ecosystems.…”
Section: Introductionmentioning
confidence: 99%